Management of Organizational Resources at the Indonesian Tennis Association in Semarang City in 2023 - Iwan Fajar Hariyanto; Soedjatmiko Soedjatmiko; Nasuka Nasuka (JUARA : Jurnal Olahraga, 2023)
The aim of this research to identify and analyze organizational resources consisting of man, money, material, methods, machine, networking and information systems in PELTI Semarang. This research is a qualitative research using ethnographic methods. Data collection techniques with observation, interviews and documentation. The results of this study 1) man for planning are not going well because there is no selection process, while organizing, actuating and supervising are going well. 2) money in this organization for planning, organizing and supervising is going well, while the actuating is not good because there are needs that do not have a budget. 3) material for planning, organizing and actuating is not going well because this organization does not yet have a tennis court while supervision is going well. 4) methods in this organization for planning, organizing, actuating and supervising goes well. 5) machine for this organization from planning, organizing, actuating and supervising activities are going well. 6) networking for this organization for planning, organizing, actuating and supervising is running well. 7) the information system for planning, organizing and supervising is running well, while the actuating is not going well.